Making meaning of whiteness : exploring racial identity with white teachers - McIntyre, Alice, 1956- (SUNY series, social context of education., 1997)
Describes how a group of white female student teachers examined their "whiteness" and developed ways of thinking critically about race and racism in educational practice. McIntyre describes how a group of white middle- and upper-middle-class female student teachers examined their "whiteness" and how they, as current and future educators, might develop teaching strategies that aim to disrupt and eliminate the oppressiveness of white privilege in education. The group analyzed ways of making meaning about whiteness and thinking critically about race and racism, and explored how racial identity is implicated in the formation and implementation of teaching practices.